Investigation of the special surface state of BaCo0.4Fe0.4Zr0.1Y0.1O3-δ vs Ba0.5Sr0.5Co0.8Fe0.2O3-δ and La0.6Sr0.4Co0.2Fe0.8O3-δ for high oxygen catalysis activity on the intermediate-temperature solid oxide fuel cell - Wang, Xiaojing; Zhang, Tonghuan; Qiu, Peng; Qi, Huiying; Tu, Baofeng (International journal of hydrogen energy, 2024)
Compared to conventional Ba0.5Sr0.5Co0.8Fe0.2O3-δ (BSCF) and La0.6Sr0.4Co0.2Fe0.8O3-δ (LSCF), BaCo0.4Fe0.4Zr0.1Y0.1O3-δ (BCFZY) with special surface species and structure can exhibit a distinctive compromise between the redox activity and cell stability. The X-ray photoelectron spectroscopy (XPS), temperature-programmed desorption (TPD) and infrared spectrum (IR) results suggest that besides the oxygen species of BSCF and LSCF, the OH-related species can be detected on BCFZY, which can play a promoting role in oxygen catalysis activity. The O2− -conducting solid oxide fuel cell (SOFC) with BCFZY cathode shows the superior power densities at intermediate temperatures (750-650 °C), which are 1.2–1.6 times than those of BSCF cell, and 1.8–2.1 times than those of LSCF cell. Distribution of relaxation times (DRT) analysis on three symmetric cells and three single cells reveal that BCFZY cathode shows superior oxygen adsorption and dissociation, which can be ascribed to the peculiar OH-related species and multiscale structure on the surface. The cell with BCFZY cathode can remain the stable performance during the discharge testing at 650 °C for 240 h, indicating a reliable surface state to promote both oxygen catalysis activity as well as the performance stability for O2− -conducting SOFC. •BCFZY demonstrates considerable activity vs BSCF and LSCF on O2--conducting SOFC.•BCFZY cell achieves high power density (1.99–1.40 W cm−2) at 750-650 °C.•BCFZY cathode exhibits superior oxygen exchange processes on surface.•The special surface state of BCFZY cathode improves O2 catalysis and stability.